An experimental inquiry into the effect of yardstick competition on corruption - Viceisza, Angelino (International Food Policy Research Institute, 2008)
This study reports theory-testing laboratory experiments on the effect of yardstick competition on corruption. The results reveal that on the incumbent's side, yardstick competition acts as a corruption-taming mechanism only if the incumbent politician is female. On the voter's side, voters focus on the difference between the tax rate in their own jurisdiction versus that in another jurisdiction. If the voters' tax rate is deemed unfair compared to that in the other jurisdiction, voters are less likely to re-elect. These findings support the claim by Besley and Case (1995) that incumbent behavior and tax setting are tied together through the nexus of yardstick competition, suggesting that our laboratory experiments have some external validity.